Performance evaluation in competence-based learning model in higher education scenarios using social network: a case study - Katherina Edith GALLARDO CÓRDOVA; María Eugenia GIL RENDÓN; Alejandra Laura GOVEA GARZA (Ediciones Universidad de Salamanca, 2017)
A research about performance evaluation was conducted in a graduate online course designed in the Based-Competency Model. Facebook was used as a social and interactive tool that would permit sharing information to illustrate various aspects of diverse educational contexts as well as the impacts of the implementation of improvement projects seen from the beneficiaries' perspective. Case Study was the methodology selected. Postgraduate students got the task to work on certain improvements on learning assessment matters. The educational scenarios were located in Mexico and Colombia. 7 units of analysis were chosen among 34 possible. The findings pointed out that students worked on their contexts in alignment with the stipulated academic competencies. The use of video materials posted and shared using Facebook allowed get a deeper understanding of the way the benefits influenced in each of the educational communities. Besides, these products evidenced students' appropriate performance. In conclusion, the use of social networks for fortifying performance assessment is highly recommended. Moreover, it is expected that these benefits also influence some of the curricular and instructional design aspects.